Economic Policy in Russia: Factors and Constraints - BOLSHAKOV, Sergey Nikolaevich; BOLSHAKOVA, Yulia Mikhailovna; TKACHEV, Sergey Alekseevich; ZARUBIN, Valery Grigorievich (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The protracted economic crisis caused by falling oil prices and lack of competitiveness of the Russian economy determines the value of predictive assessments of economic development. Scenario modeling of options for the development of Russian economy in the medium term allows to reveal the trends and the likely priorities of economic development, as well as measures of Russian state authorities. The article assesses the macroeconomic indicators of economic development, records a drop in effective demand and consumer sentiment index. The growth of problems associated with the budget deficit and the performance of the state's social obligations is analyzed. The dynamics of the state of the National Welfare Fund and the direction of fund investment are analyzed; and political motivation of spending public funds and resources is stated.